Factors Contributed of Breast Cancer for Women in Iraq - Marghoob Hussein Yaas1 Rebaz Ismael Ali Al – Brzanji2 , Mohammed Abdual Magead Mohammed3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background and aim: Breast cancer is abnormal growth of breast cells, result from spurts or abnormalchanges genetic that responsible for cell growth and maintain its health. It is one of the most dangerouscancers that affect woman and reports high level of morbidity yearly if not treat early.The study aimed to assess the Factors that Contributed of Breast Cancer for Women.Materials and method: A descriptive design was employed through the present study from November 1st2017 to March 20th 2018, which carried out on four Health Directorates of different Governorates; (SalahAlden, Kirkuk, Diyala and Sulaymaniyah).Assessment questioner consist of two parts contains of women socio-demographical characteristic, the otherpart concerning of the assessment the risk factors that contribute breast cancer. A non-probability sample(purposive approach) is selected for the study which includes (88) women diagnosed with breast cancerwere treated in Hospital or Nuclear centers, or the patients who visited the outpatient clinic in the samehospital or specialist center for medical follow–up and treatment. Data were gathered through the patients`interviewed. Content validity of the questionnaire was done through eliciting the opinions of a panel of (10)expert, while the reliability of this tool is determined through application of a pilot study by using internalconsistency through the computation of the Cronbach alpha correlation coefficient of the scale on datagathered from patients.Results: The overall results revealed that most women were adult (42.0%) married (72.7%) with loweducational level and they lives in urban (64.8%) with sufficient income (40.9%). Most sample`s work washouse wife (64.7 %), and about half of sample were feed his children natural feed. (35. 2 %) were normalbody weight and (21.5 %) of high weight.Conclusion: Most women depended on a style of food contain :( fat, kidneys, red meat, dairy product andsalt) that will be contributed to breast cancer development. Greatest women experience of psychologicalproblems and don’t compliance of breast self-examination every month.